STRATEGI PENGEMBANGAN OBJEK WISATA AIR PANAS DI DESA MAROBO, KABUPATEN BOBONARO, TIMOR LESTE - Barreto, Mario; Giantari, I.G.A. Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.11.TAHUN 2015, 2016)
The tourism is a new type of industry which able to bring up economic growth rapidly in providing jop opportunity, increasing income, living standard, and estimulate another productive sectors. When the object of hot spring is well developed, it can lift up the national income and local revenue in order to improve the welfare and prosperity of society. This study aimed to analyze the tourism development strategy of hot spring  in  Marobo village, of  Bobonaro District. This study used 10 people a sample from government, community leaders and businessmen. Data were collected by conducting interviews and questionnaires. Subsequently collected data were analyzed by using descriptive analysis and SWOT analysis as well as internal and external matrix (IE). The result of this study showed that the analysis of the external environment, obtained a value of 3.91 and internal environment of 3:03. So the adequate development strategy can be applied is tourism development such as in the period  Merry  Christmas and New Year Day with competite  price and more varied so as to meet the target. Tourism development can be done by diversifying tourism objects and system modifications so enable tourists to have travel easily. The result of  the study as mentioned above reminds all relevant parties to have  serious attention on the development of Marobo hot spring. In order to make the tourism object as modern and attractive destination, it is  advised to all relevant parties to upgrade the cooperation with  Travel Agencies and Investors in providing the widely opportunities tho the development of the tourism object. In addition, it is necessary to advice to government to recruit employees who are espesialized in the are of tourism. It is important to advice also the government at Municipality level in particularly The Official Tourism and Culture of Bobonaro to be able to activate the website optimally on potential attractions of Marobo Hot Spring.
Keywords: Estrategy, Development, Tourism Object, Hot Spring, Marobo